A study of the problem of phosphorus deficiency in South Africa mainly in relation to its effect on the phosphorus content of the blood of animals - Malan, Avril Are (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc.) -- University of Stellenbosch, 1930.